Incorporation and stability of carotenoids in a functional fermented maize yogurt-like product containing phytosterols - Gies, Magali (2019)
A functional yogurt-like product based on fermented maize enriched in carotenoids and phytosterols was developed to be an alternative to existing functional dairy products. Incorporation and stability of fat-soluble compounds were challenging in this complex matrix. Moreover, it is known that phytosterols decrease carotenoids absorption, but this decline can be offset by increasing carotenoids in foodstuffs. Thus, the aims of this work were to optimize the manufacturing process of a fermented yogurt-like product containing phytosterols by incorporating carotenoids taking into account two Lactobacilli strains as starters. The stability of β-cryptoxanthin, β-carotene and lycopene was studied during the whole process in order to confer a nutritional balance between them and phytosterols. After 15 h of ermentation, a starter ratio 50-50 (L. plantarum-L. casei) gave the best final biomass with 109 CFU/g necessary to obtain a probiotic potential. Relative carotenoid losses (20–27%) occurred during the pasteurization step while no negative impact on carotenoids was due to fermentation. Fatsoluble compounds remained relatively stable during the whole process with 75% of retention. These results suggest that incorporation and stability of carotenoids in a fermented-maize yogurt-like product containing phytosterols are necessary steps to induce a cholesterol-lowering effect without detrimental effects on carotenoids